PENERAPAN METODE BRAINSTORMING MEDIA GAMBAR TERHADAP HASIL BELAJAR SISWA PELAJARAN SEJARAH MA MATHLA’UL ANWAR PONTIANAK - Habib Al - ham; Sulistyarini Sulistyarini; Ika Rahmat (Universitas Tanjungpura, 2020)
AbstractThis study aims to determine the effect of the application of Image Media Assisted Brainstorming Method to the learning outcomes of students of class X IIS 3 Madrasah Aliyah Mathla'ul Anwar Pontianak. This study used the Quasi Experimental method with the design of